Kitosan dari limbah udang sebagai bahan pengawet ayam goreng - Ratna Sri Harjanti (Jurnal Rekayasa Proses, 2014)
Shrimp industries have to deal with shell solid waste. On the other hand, this shell solid waste can be utilized to produce citin and citosan. One of the beneficiations of citosan is for food preservation. This ability is based on the existence of poly cation with positive charge that is responsible for the inhibition of bacteria growth. In this study, NaOH was varied to produce citosan from shrimp shell resulting rendemen and deasetilation degree. Deproteination of the shrimp shell was done using NaOH (3,5% b/v) for 2 hours, at temperature of 65°C, while demineralization was conducted using HCl 1 N (1 gram of sample: 15 mL of HCl) for 1 hour at room temperature. Deasetilation was done by heating citin in NaOH with concentration of 30%, 40%, 50%, and 60% b/v for 4 hours at temperature of 100°C. Further, observation on the ability of resulted citosan as food preservation was conducted. Chicken meat was choosen as sample to represent the abundance restaurants selling these product. It has been found that citosan from shrimp shell solid waste can be utilized as food preservation agent for chicken meat without changing the taste and texture of the meat. The optimum condition is 45 minutes with citosan concentration of 2% with deasetilation degree of 70,34%.